Optimal neoadjuvant chemotherapy duration in Wilms tumour with intravascular thrombus: A literature review and evidence from SIOP WT 2001 trial. Issue 11 (24th July 2019) - Morris, Louise; Squire, Roly; Sznajder, Beata; van Tinteren, Harm; Godzinski, Jan; Powis, Mark
Abstract: Introduction: Preoperative chemotherapy is recommended for children with Wilms tumour with intravascular extension. Extended chemotherapy may improve resectability, but increase tumour adherence to vascular endothelium, precluding complete resection. To evaluate the optimal length of preoperative treatment, we report a two‐part review comprising systematic review of the literature and investigation of patients treated in the International Society of Paediatric Oncology (SIOP) WT 2001 trial. Methods: Studies were identified using Medline and Embase databases from 1996 to present. English language titles reporting management of intravascular Wilms tumour were analysed. Patients with Wilms tumour and thrombus were identified from the SIOP WT 2001 trial. Overall survival (OS) and event‐free survival (EFS), tumour regression, completeness of resection and cavectomy were investigated. Results: The search retrieved 43 articles documenting 498 children. Note that 72% of the patients received neoadjuvant chemotherapy: 101 received standard course (4‐6 weeks, standard course neoadjuvant chemotherapy [StC]) and 62 extended course (> 6 weeks, extended course neoadjuvant chemotherapy [EC]). There was no significant difference between the groups in terms of thrombus regression or completeness of resection. EFS was greater in the StC group (78 vs 54%; P  = .04). Of 4511 patients registered in the SIOP WT 2001 trial, 166 had thrombus. Note that 97% of the patients received neoadjuvant chemotherapy: 63 StC and 67 EC. There was no significant difference between the groups with regard to tumour regression, complete resection, or cavectomy. Survival was significantly higher in those receiving StC than EC (OS: 95% vs 82%, P  = .025; EFS: 88% vs 72%, P  = .047). Conclusion: There is no evidence that prolonged courses of neoadjuvant chemotherapy beyond the recommended protocols confer any additional benefit in treating intravascular extension of Wilms tumour.